Estudo imuno-histoquímico da co-expressão de citoqueratinas, vimentina e actina em neoplasias de glândula salivar - Carvalho, Yasmin Rodarte [UNESP] (Universidade Estadual Paulista (Unesp), 1998)
Human salivary gland tumors originated from intercalated ducts present a broad range of histologic and cytologic patterns, mainly due to the presence of myoepithelial cells. The aim of this study is to verify the differentiation grade of neoplastic cells and a possible relation between myoepithelial cell differentiation and the presence of luminal secretory contents. The expression of vimentin and cytokeratin (CK) intermediate filaments, actin myofilament and epithelial membrane antigen (EMA) was investigated by double labeling immunocytochemical technique, in thirty salivary gland neoplasms: 5 pleomorphic adenomas, 5 myoepitheliomas, 3 basal cell adenomas, 7 adenoid cystic carcinomas (ACC) and 10 polimorphous low grade adenocarcinomas (PLGA). Tumors with intercalated duct differentiation (pleomorphic adenomas, basal cell adenomas and ACC) express CKs 7, 8, 18 and 19 in the luminal cells and coexpress eventually CK14 with these CKs. Some luminal cells stained with anti-EMA antibody, mainly where a secretory content in the lumen was observed. Outer ductal cells and other myoepithelial-like cells express vimentin, sometimes coexpressing actin and/or CK14 with vimentin. Plasmacytoid cells in myoepitheliomas and pleomorphic adenomas express vimentin and rarely CKs 7, 8, 18 and 19, sometimes coexpressing these CKs with CK14 but they are negative for the remaining antigens. Tumors without intercalated duct differentiation (solid basal cell adenoma and PLGA) express vimentin and CKs 7, 8, 14 and 18, sometimes coexpressing CKs 8 and 18 with CK14. In conclusion, in tumors with intercalated duct differentiation, myoepithelial cells express vimentin and sometimes coexpress actin and/or CK14 with vimentin, never coexpressing other CKs with vimentin. CK14 and actin are independently expressed by myoepithelial cells, so their expression is probably induced by different stimulus. However, the secretory function of luminal cells, visualized by EMA staining, ....

Os tumores de glândulas salivares humanas originados do ducto intercalar apresentam grande variação histológica e citológica, atribuída principalmente à presença da celula mioepitelial. Neste estudo, pesquisou-se a presença dos filamentos intermediàrios vimentina e citoqueratina, de microfilamentos de actina e do antígeno epitelial de membrana (EMA), em 30 neoplasias originadas do ducto intercalar: 5 adenomas pleomórficos, 3 adenomas de celulas basais, 5 mioepiteliomas, 7 carcinomas adenóide císticos (CAC) e 10 adenocarcinomas polimorfos de baixo grau de malignidade (APBGM), com o intuito de verificar o grau de diferenciação das células neoplásicas e uma possível relação da diferenciação mioepitelial com a presença de secreção intra-luminal. Foram realizadas reações imuno-histoquímicas para dupla evidenciação de antígenos. Nas neoplasias em que há diferenciação para ducto intercalar (adenoma pleomórfico, adenoma de células basais e CAC), as células luminais expressam as citoqueratinas 7, 8, 18, 19 e eventualmente co-expressam a citoqueratina 14. Alguns ductos apresentam celulas luminais positivas para EMA, especialmente quando há secreção em seu lúmen. As células externas das estruturas ductais e demais células com características mioepiteliais expressam vimentina e co-expressam eventualmente actina e/ou citoqueratina 14, sendo sempre negativas para as demais citoqueratinas e para EMA. A co-expressao de actina, vimentina e citoqueratina 14, nas células externas das estruturas ductais, e mais comum quando a célula luminal é positiva para EMA. As células plasmocitóides, presentes no mioepitelioma e no adenoma pleomórfico, expressam vimentina e raramente as citoqueratinas 7, 8, 18 e 19, eventualmente co-expressando a citoqueratina 14, e são negativas para os outros antígenos pesquisados. Nos tumores em que não há diferenciação para ducto intercalar (APBGM e adenoma de células basais sólido) ...
Keywords: Glandulas salivares; Imuno-histoquímica; Neoplasias bucais; Cancer